Transforming Islamic Religious Education: Active Learning Strategies for Fostering Religious Moderation at SDN 2 Serangan - Zainuri, Moh; Mashudi, Mashudi; Turmudzi, Imam (ATTA`DIB, 2025)
This study aims to explore how active learning strategies in Islamic Religious Education (IRE) can foster the internalization of religious moderation values at SDN 2 Serangan, Denpasar. Using a qualitative approach with a case study method, data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis. The findings indicate that the implementation of active learning strategies such as group discussions, case studies, and storytelling significantly contributed to instilling values of tolerance, mutual respect, and peaceful coexistence among students. The IRE teacher served as both a facilitator and a moderation agent, contextually linking Islamic teachings to the students' socio-religious realities. The participatory learning model, supported by inclusive school policies, created an educational environment conducive to promoting religious moderation. This study concludes that transforming IRE through active learning strategies is an effective approach to developing moderate character in students from an early age.